The positioning of spoken language as a key (badly-needed) educational notion - Daszkiewicz, Michał (Papers in Linguistics, 2025)
This paper introduces the notion of spoken language positioning, which has remained unrecognised but has the potential of affecting educational systems altogether on many different levels. The text covers the notion through four sections on how to understand, present, study, and implement the eponymous notion, respectively. Hence, the text first discusses the character and significance of positioning in education, exemplifying it with spoken language. Then, it presents how the notion serves as grounds for a holistic approach to spoken language, viewed in positivist terms as a concept or as an individually shaped construct. Four rules are formulated here as following from the holistic view. This is followed by an analysis of how the positioning of spoken language, as a hybrid, can be studied, with two complementary types of methodologies. The hybrid type of research is proposed as covering two stages, one (‘Generalisation’) complying with the positivist regime and the other one (‘Specification’) – with the constructivist rationale. The paper closes with a discussion of what the notion of positioning unravels for entire educational systems, how – despite its absence in educational science – paradigmatic a notion it is, and how it complements, follows and expands that of knowledge construction.